2018
DOI: 10.3389/fpsyg.2018.01208
|View full text |Cite
|
Sign up to set email alerts
|

Synchronization in Singing Duo Performances: The Roles of Visual Contact and Leadership Instruction

Abstract: Interpersonal synchronization between musicians during ensemble performances is characterized by continuous micro-timing adjustments due to intentional and unintentional factors supporting expressive interpretations, or caused by noise during the cognitive-motor process. Whether visual contact between musicians and the instruction to act as leader or follower affect synchronization in ensembles remains mostly unclear. This study investigates the role of visual cues and leader-follower relationships in singing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 29 publications
4
36
0
Order By: Relevance
“…Recently, a few studies have investigated the role of visual contact and rehearsal on interpersonal synchronization between singers during singing ensemble performances. Research demonstrated that synchronization was better with visual contact between singers than without during singing duo performances [14], and improved between the first two rehearsals in a singing quintet rehearsing a homophonic piece across five rehearsal sessions during a four-month period [15]. However, whether listeners with different levels of expertise can perceive the effects of visual contact between singers and varying levels of rehearsal on the interpersonal synchronization between singers during ensemble performance has not yet been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a few studies have investigated the role of visual contact and rehearsal on interpersonal synchronization between singers during singing ensemble performances. Research demonstrated that synchronization was better with visual contact between singers than without during singing duo performances [14], and improved between the first two rehearsals in a singing quintet rehearsing a homophonic piece across five rehearsal sessions during a four-month period [15]. However, whether listeners with different levels of expertise can perceive the effects of visual contact between singers and varying levels of rehearsal on the interpersonal synchronization between singers during ensemble performance has not yet been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…6 Using the choral synthesis system described in Howard et al, 7 the tuning of student singers was analyzed as they replaced either the alto or soprano line of ''Exercise 3'' when listening to the other three parts tuned either in equal temperament or just intonation over headphones. 8 Singers produced less stable pitches across tones and were more ''out of tune'' when tuning with the justly tuned rather than the equally tempered version of the synthesis, implying that the singers in this study tended towards equal temperament.…”
Section: Introductionmentioning
confidence: 68%
“…Lx is a non-invasive, widely used method for the analysis of the singing voice. 27 It has been recently used to investigate several aspects of singing ensemble performances, such as synchronization, 26,28,29 blending, 30 and tuning, 5,6 as it allows the identification of the individual contribution of each singer. Each Lx was attached to a preamplifier (ART CleanBox Pro) to reduce noise and interference over long cable runs.…”
Section: Apparatusmentioning
confidence: 99%
See 2 more Smart Citations